Fundamentals of Accounting Losses - Klein, April; Marquardt, Carol A. (The Accounting Review, 2006)
This paper examines accounting and nonaccounting factors behind accounting losses over a 50-year period. Using multivariate time-series analysis, we report evidence that the annual percentage of losses for U.S. firms is significantly related to accounting conservatism, Compustat coverage of small firms, real firm performance as measured by cash flows from operations, and business cycle factors. We further find that nonaccounting factors tend to play the dominant role in explaining accounting losses over our sample period. Our results are robust to alternative definitions of macroeconomic productivity, as well as to varying model specifications. Our findings contribute to the literature on accounting losses and accounting conservatism and have implications for the use of accounting loss information in numerous settings.